Mechanical properties of the patellar tendon in elite volleyball players with and without patellar tendinopathy - Helland, C.; Bojsen-Moeller, J.; Raastad, T.; Seynnes, O. R.; Moltubakk, M. M. H.; Jakobson, V.; Visnes, H.; Bahr, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Patellar tendinopathy (PT) has an estimated prevalence of 40-50 % among elite volleyball players (Lian, Engebretsen & Bahr, 2005). The risk factors and functional consequences of this overuse injury are not fully understood. The aims of the present study were to determine whether PT affects tendon mechanical properties in elite volleyball players, and whether potential changes in these properties impair jumping performance. Methods: 20 healthy and 20 male volleyball players with PT were identified from a 5-year prospective cohort study on junior elite volleyball players. Subjects were evaluated with respect to maximal vertical jump performance and patellar tendon mechanical properties were examined using Ultrasonography (US) and Magnetic Resonance Imaging (MRI). An unpaired t-test was applied to evaluate group differences with an alpha level of 0.05. Results: Preliminary results indicate that the PT group jumped significantly higher than controls in counter movement jumps (CMJ) and spike jump (SPJ) compared to the control group, PT: 44.0 ± 4.6 cm and 81.5 ± 6.1 cm vs. control: 39.1 ± 4.3 cm and 75.2 ± 7.1 cm, respectively (p<0.05, n = 24). CMJ-SJ ratio was greater in PT compared to the control group; 4.0 ± 2.1 vs. 1.6 ± 1.9 (p<0.05). No differences were found in patellar tendon stiffness between the two groups (n =14). No differences were found in patellar tendon length between the two groups. Discussion: Although mechanical properties were similar between groups, it may be speculated that differences exist in material properties (decreased Young`s modulus in PT) as a result of the increased cross-sectional area (CSA) of the injured tendon. The differences in jump performance between the groups seem to correspond to earlier findings linking PT prevalence to higher jumping performance and therefore greater loading and/or more intense jump training (Lian, Refsnes, Engebretsen, & Bahr, 2003; Visnes & Bahr, 2012). Importantly, these results indicate that jumping performance in elite volleyball players with PT is not impaired beyond the level of a matched control group.